A hybrid AHP-VIKOR methodology to evaluate for adoption COTS database components based on usability. (2017) - Rawashdeh, Adnan; Matalkah, Bassem; Hammouri, Awni
Reusing commercial off-the-shelf (COTS) components in large system development provides several benefits, including accelerated development, increased dependability, and reduced process risk. However, choosing the right component among multiple alternatives is considered a hard process and may involve risk. Throughout the development life cycle, many stakeholders contribute from their own perspectives, and interests. End users desire ease of use, which is a user-focused quality attribute. Under such circumstances, there should be a mechanism that helps stakeholders to make decisions accordingly. Multiple-criteria decision-making (MCDM) or multiple-criteria decision analysis (MCDA), a sub-discipline of operations research, explicitly evaluates multiple conflicting criteria in decision-making. This research work introduces a decision-making methodology application that employs two well-known MCDM techniques, namely Analytic Hierarchy Process (AHP) and Vise Kriterijumska Optimizacija I Kompromisno Resenje (VIKOR). Combining AHP and VIKOR enables the new model to effectively select the best alternative from among a range of COTS components.